Effect of Hydrofluoric Acid Etching on Performance of Si/C Composite as Anode Material for Lithium-Ion Batteries. (17th October 2018) - Su, Mingru; Liu, Shuai; Li, Jinlin; Dou, Aichun; Feng, Weihang; Bai, Jinchuan; Liu, Yunjian
Abstract : The effect of hydrofluoric acid (HF) etching on the performance of Si/C anode was extensively studied in terms of the structural stability, morphology, element distribution, and electrochemical properties. XRD results show that the diffraction peaks of silicon got weakened after being etched by HF. SEM images reveal that the morphology of the composite became coarse after being etched by HF. EDS mapping illustrates the distribution of elements before and after HF etching. Electrochemical studies show that HF etching can improve the cycling performance of Si/C composite but exhibit a deleterious effect on capacity. The results indicate that HF etching could be a promising method for enhancing the performance of silicon-based materials.